PENGEMBANGAN DIGITALISASI DAN PENATAAN ARSIP KEPENDUDUKAN DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SURABAYA - Ronan Agung Ramadita Aziz; Rendy Dwi Adi Putra (Gapenas Publisher, 2022)
This study aims to determine the innovations developed in the implementation of archiving birth certificates at the Department of Population and Civil Registration of the City of Surabaya. Electronic archives have an important role in the administrative system, besides that they are also legal evidence based on Law Number 11 article 5 paragraph (1) of 2008. The development of information technology requires records to be processed electronically. In this study, the author uses an exploratory method. This method is used because the author does not yet know a clear picture of the problem situation that occurs in the field. The method of implementing the activities carried out are Observation, and Documentation. The results showed that the archive arrangement system was still not good and still conventional. It is very necessary to make improvements, so that documents can be neatly organized, and not messy and if needed at any time are easy to find again